2012
DOI: 10.1097/01.asw.0000421460.21773.7b
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the High-Risk Diabetic Foot

Abstract: People with diabetes mellitus will develop lower-limb complications, such as neuropathy, peripheral vascular disease, foot ulcers, and lower-leg amputations. Resources to control elevated hemoglobin A1c and blood pressure, along with the standardized approach using the 60-second tool (2012), can detect the high-risk diabetic foot and help prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
0
36
0
3
Order By: Relevance
“…Previous studies of persons with diabetes have identified neuropathy (loss of protective sensation), peripheral vascular disease, prior foot ulcer, or previous amputation as risk factors for developing a foot ulcer [2] . Although optimal diabetes control reduces chronic complications, actual provision of diabetes care frequently falls short of accepted guidelines [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of persons with diabetes have identified neuropathy (loss of protective sensation), peripheral vascular disease, prior foot ulcer, or previous amputation as risk factors for developing a foot ulcer [2] . Although optimal diabetes control reduces chronic complications, actual provision of diabetes care frequently falls short of accepted guidelines [3] .…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The Inlow's 60 second foot examination tool is used for the examination of diabetic patients' foot. 30 For a healthy well-being and optimal wound healing, comprehensive wound screening tools are important. The 60 second foot screening tool is developed by researchers as a simple tool that can screen diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly due to a better understanding of the causative pathway leading from a foot ulcer to amputation, but specifi c determinants of this decrease are unknown [4,5]. Diabetic foot care has been recognised as a relevant problem and a lot of local strategies have been implemented in the last decade [6]. Especially in Germany, diabetic foot networks have been developed and built up eff ective structures [7].…”
Section: Introductionmentioning
confidence: 99%